Działalność innowacyjna przedsiębiorstw a jakość miejsc pracy - Węgrzyn, Grażyna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The paper attempts to define the impact of growing innovation activity of enterprises on the quality of jobs they offer. It provides assessment of the developments taking place in the most innovative sectors of Polish economy in the aspects of: - remuneration paid, - types of contract offered, - employee qualification level, - opportunities for career development. The new technologies on one hand enforce, and on the other allow the emergence of new, non-standard forms of employment. The proportion of contracts for a specific period or for a specific task increases, while the number of permanent job offers decreases. The developments seen in economy due to innovation are so dynamic that the traditional system of school-based education cannot accommodate them and adjust to the needs of the economy and the labour market. This makes the development of lifelong learning necessary, as continuing education will be decisive for job security. The conducted analysis shows that the average salary offered by the industries considered most innovative in 2005 did not differ much from the national average. However, all the innovative industries have improved the employment conditions offered. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1191, s. 695-705